Artificial miRNAs Reduce Human Mutant Huntingtin Throughout the Striatum in a Transgenic Sheep Model of Huntington's Disease - Pfister, Edith L; DiNardo, Natalie; Mondo, Erica; Borel, Florie; Conroy, Faith; Fraser, Cara; Gernoux, Gwladys; Han, Xin; Hu, Danjing; Johnson, Emily; Kennington, Lori; Liu, PengPeng; et al. (Human gene therapy, 2018)
Huntington's disease (HD) is a fatal neurodegenerative disease caused by a genetic expansion of the CAG repeat region in the huntingtin (HTT) gene. Studies in HD mouse models have shown that artificial miRNAs can reduce mutant HTT, but evidence for their effectiveness and safety in larger animals is lacking. HD transgenic sheep express the full-length human HTT with 73 CAG repeats. AAV9 was used to deliver unilaterally to HD sheep striatum an artificial miRNA targeting exon 48 of the human HTT mRNA under control of two alternative promoters: U6 or CβA. The treatment reduced human mutant (m) HTT mRNA and protein 50-80% in the striatum at 1 and 6 months post injection. Silencing was detectable in both the caudate and putamen. Levels of endogenous sheep HTT protein were not affected. There was no significant loss of neurons labeled by DARPP32 or NeuN at 6 months after treatment, and Iba1-positive microglia were detected at control levels. It is concluded that safe and effective silencing of human mHTT protein can be achieved and sustained in a large-animal brain by direct delivery of an AAV carrying an artificial miRNA.
Keywords: Injections; játra; large animal models; Sheep; RNAi; ovce; Humans; genetické vektory; protein huntingtin; messenger RNA; Electrolytes; Huntingtonova nemoc; MicroRNAs; Huntington's disease; geneticky modifikovaná zvířata; genom virový; ledviny; Mutant Proteins; AAV; mutantní proteiny; Kidney; lidé; injekce; zvířata; neurony; Neostriatum; RNA, Messenger; Animals, Genetically Modified; Huntington Disease; neostriatum; Genome, Viral; Liver; Immunoassay; elektrolyty; mikroglie; Microglia; Neurons; Huntingtin Protein; Genetic Vectors; mikro RNA; Animals; imunoanalýza; Disease Models, Animal; Dependovirus; modely nemocí na zvířatech